2020
DOI: 10.31223/osf.io/e69bz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The environmental impacts of palm oil in context

Abstract: Delivering the Sustainable Development Goals (SDGs) requires balancing demands on land between agriculture (SDG 2) and biodiversity (SDG 15). The rapidly increasing production of vegetable oils in general, and palm oil in particular, is perhaps the most controversial illustration of these trade-offs. We review palm oil production in the context of global vegetable oil crops and identify a wide range of negative environmental and biodiversity impacts. Oil palm, however, generally produces more oil per area tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…However, from 2001 to 2017 conversion increased, accounting for 36% of total deforestation in Kalimantan 12 . These studies demonstrate that the impacts of oil palm on forests clearly vary by region and period 13 . Several recent studies have demonstrated that industrial plantation expansion and associated forest conversion had slowed 10,12 though not everyone agrees 14 .…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…However, from 2001 to 2017 conversion increased, accounting for 36% of total deforestation in Kalimantan 12 . These studies demonstrate that the impacts of oil palm on forests clearly vary by region and period 13 . Several recent studies have demonstrated that industrial plantation expansion and associated forest conversion had slowed 10,12 though not everyone agrees 14 .…”
Section: Introductionmentioning
confidence: 67%
“…Furthermore, an increasing number of consumers seek products that they consider ethical. This has generated various initiatives aimed at distinguishing and certifying products that avoid deforestation, and companies seeking to be associated with pledging to avoid forest clearing with "no-deforestation commitments" 13 . This interest has led to wide scrutiny of the palm oil industry using data that now include publicly available satellite imagery in near-real time 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific studies add force to the growing preference for tenure-based approaches to limit encroachment, fires, and logging, while also securing livelihood support for communities (Levy-Tacher et al 2019;Oldekop et al 2019;Tseng et al 2021). Research on the expansion of mining and its impacts upon forests and biodiversity calls for community land ownership as a means to help contain losses (Meijaard et al 2020;Vallejos et al 2020). In 2019 a group of 20 geospatial scientists and the Intergovernmental Panel on Climate Change independently concluded that secure customary tenure has strong potential to advance climate mitigation at scale (Garnett et al 2018;IPCC 2019).…”
Section: Community Forest Ownershipmentioning
confidence: 99%
“…In 2019, Malaysia exported a total of 2.09 million tonnes of palm oil to the EU-up 9.5% from 1.91 million tonnes recorded in 2018-and accounting for 11.3% of Malaysia’s total 2019 palm oil exports. However, the European Parliament resolution of 4th April 2017 decreed that, due to concern on oil palm’s impact on the environment and biodiversity, palm oil will be phased out by the EU for use as transport fuel in 2021 [ 1 , 17 , 18 , 19 ]. This decision was made even though EU had made a commitment to purchase only certified sustainable palm oil that is traceable from the year 2020 onwards.…”
Section: Introductionmentioning
confidence: 99%